2024
DOI: 10.1038/s41598-024-54201-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antioxidant activity and phytochemical content of five extracts of Pleurotus ostreatus (oyster mushroom)

Magdalene Eno Effiong,
Chidinma Precious Umeokwochi,
Israel Sunmola Afolabi
et al.

Abstract: Reactive oxygen species reacts with numerous molecules in the body system causing oxidative damage, which requires antioxidants to ameliorate. Pleurotus ostreatus, a highly nutritious edible mushroom, has been reported to be rich in bioactive compounds. This study evaluated the comparative antioxidant activity and phytochemical contents of five extracts of P. ostreatus: aqueous (AE), chloroform (CE), ethanol (EE), methanol (ME) and n-hexane (HE). The phytochemical composition and antioxidant activity of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…41 The GC-MS prole of the phytocompounds from the ve extracts of P. ostreatus revealed that chloroform solvent extracted more versatile compounds compared to other solvents. This is similar to the reports by Effiong et al 42 Overall the GC-MS identied bioactive compounds in P. ostreatus have been found to possess numerous medicinal and biological signicance ranging from anti-tumor, antioxidant, anti-cancer, anti-diabetic, antimicrobial, anti-inammatory, immunomodulatory, antimalarial, probiotic, neuroprotective, anti-tuberculosis, etc.…”
Section: Gc-ms Prole Of P Ostreatus Bioactive Compounds and Their Bi...supporting
confidence: 90%
“…41 The GC-MS prole of the phytocompounds from the ve extracts of P. ostreatus revealed that chloroform solvent extracted more versatile compounds compared to other solvents. This is similar to the reports by Effiong et al 42 Overall the GC-MS identied bioactive compounds in P. ostreatus have been found to possess numerous medicinal and biological signicance ranging from anti-tumor, antioxidant, anti-cancer, anti-diabetic, antimicrobial, anti-inammatory, immunomodulatory, antimalarial, probiotic, neuroprotective, anti-tuberculosis, etc.…”
Section: Gc-ms Prole Of P Ostreatus Bioactive Compounds and Their Bi...supporting
confidence: 90%